Persistent local raw material transport at Shuidonggou Locality 2. (December 2019) - Lin, Sam C.; Peng, Fei; Zwyns, Nicolas; Guo, Jialong; Wang, Huimin; Gao, Xing
Abstract: Recent methodological development indicates that the lithic cortex to volume proportion of Shuidonggou Locality 2 published in an earlier paper (Lin et al., 2019) was erroneous. Here, we describe the issue of the original method and report the revised assemblage cortex to volume ratios of the site. The updated result suggests a pattern of persistent artifact transport in the place-use history of Shuidonggou Locality 2 during late Marine Isotope Stage 3.